2010
DOI: 10.1158/0008-5472.sabcs10-pd03-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD03-06: Clinical and Biologic Effects of Metformin in Early Stage Breast Cancer

Abstract: Background: Numerous epidemiological and pre-clinical studies have associated potential antineoplastic activity with the antidiabetic drug metformin in various tumor types including breast cancer (BC). We are conducting a neoadjuvant “window of opportunity” study to examine biologic and clinical effects of metformin in early stage BC. Data from a planned interim analysis are presented here. Materials and methods: 15 of planned 40 non-diabetic women < 75 yo with newly diagnosed untreated B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In a recent study, low doses of metformin (250 mg/day) reduced the number of rectal aberrant crypt foci (a surrogate marker for colorectal cancer) and decreased the proliferative activity of colonic epithelium in non-diabetic patients [ 31 ]. Furthermore, interim analyses of ongoing studies involving neoadjuvant metformin treatment of newly diagnosed breast cancer patients have demonstrated that metformin is safe and well tolerated, and exhibits favorable effects on insulin metabolism and tumor cell proliferation and apoptosis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, low doses of metformin (250 mg/day) reduced the number of rectal aberrant crypt foci (a surrogate marker for colorectal cancer) and decreased the proliferative activity of colonic epithelium in non-diabetic patients [ 31 ]. Furthermore, interim analyses of ongoing studies involving neoadjuvant metformin treatment of newly diagnosed breast cancer patients have demonstrated that metformin is safe and well tolerated, and exhibits favorable effects on insulin metabolism and tumor cell proliferation and apoptosis [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…42,[45][46][47][48][49] Moreover, interim analyses of ongoing studies in breast cancer patients demonstrated that metformin is safe and well tolerated, and exhibits therapeutic effects on insulin metabolism, tumor cell proliferation, and apoptosis. 50,51 Besides humans, metformin also displays significant growth inhibitory effects in numerous in vitro and in vivo animal models of carcinogenesis. In an in vitro cell culture model, metformin inhibited the proliferation of a variety of cancer cells, such as breast, prostate, colon, endometrial, ovarian, and glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin (1000 mg twice daily) was well tolerated and caused a significant reduction in Ki-67 staining in tumours and altered the expression of numerous genes including those involved in metabolism, inflammation and AMPK (PRKAA) and mTOR signalling. Interim data from additional ongoing neoadjuvant studies on breast cancer have provided evidence that metformin administration (in standard clinical dose) to newly diagnosed breast cancer patients is safe and has favourable effects on tumour cell proliferation and apoptosis in the absence of other anti-cancer treatment , Niraula et al 2010. Furthermore, Hosono et al (2010) have reported a randomised trial showing that a very low dose of metformin (250 mg daily) reduces proliferation and aberrant crypt foci formation in the rectal epithelium of non-diabetic patients with previous colorectal polyps when compared with placebo.…”
Section: Clinicalmentioning
confidence: 99%